Flufenamic Acid Inhibits Adipogenic Differentiation of Mesenchymal Stem Cells by Antagonizing the PI3K/AKT Signaling Pathway - Xuenan Liu; Zheng Li; Hao Liu; Yuan Zhu; Dandan Xia; Siyi Wang; Ranli Gu; Ping Zhang; Yunsong Liu; Yongsheng Zhou (Stem Cells International)
Objectives. Flufenamic acid (FFA) is a representative of the fenamic acids, an important group of NSAIDs. In the present study, we study the effects of FFA on adipogenesis of human mesenchymal stem cells (MSCs) and we explore the potential mechanism. Methods. To investigate the effects of FFA on adipogenic differentiation of hMSCs, human adipose-derived stem cells (hASCs) and human bone marrow mesenchymal stem cells (hBMMSCs), representative of hMSCs, were treated with FFA during adipogenic differentiation in vitro. The effects of FFA in vivo were evaluated using a heterotopic adipose formation assay in nude mice as well as ovariectomized (OVX) and aged mice. To explore the mechanism of FFA, Western blot was used to determine activation of the PI3K/AKT signaling pathway. Results. Our results demonstrate that, at certain concentrations, FFA inhibited adipogenesis of human MSCs both in vitro and in vivo. Mechanistically, FFA inhibited adipogenesis of human MSCs by inhibiting the PI3K/AKT pathway. Conclusions. The present study indicated that FFA could be used to inhibit adipogenesis of human MSCs in tissue engineering and diseases related to excessive adipogenic differentiation of MSCs.